CORRELATIONS BETWEEN DESIGN OF THE DENTAL IMPLANTS AND THEIR SURVIVAL RATE - Alexandru Daniel Referendaru; Costin Coman; Raluca Monica Comăneanu; Anca Iuliana Popescu; Horia Mihail Barbu (Amaltea Medical Publishing House, 2021)
Objectives. The study aimed to establish correlations between implant geometry, bone density and survival rate of implant therapy. Material and method. The study material consisted of medical documents (clinical observation and treatment sheets, which included both the results of recommended laboratory tests, photographs and imaging investigations performed pre / intra / postoperatively) of patients who were addressed between October 1st, 2014 and October 1st, 2018 to the Oral Rehabilitation Clinic "Prof. Dr. Barbu". The study included patients wearing mobilizable prostheses, with advanced periodontal diseases that required tooth extraction, patients who accepted dental implants as a treatment solution and presented at all scheduled sessions, including long-term post-therapeutic dispensary of at least 1 year. Statistical processing was performed with Microsoft Excel 2016. Results. The study group included 73 patients of both sexes (28 men and 45 women), old carriers of mobilizable prostheses, with severe periodontal diseases, which required dental extractions. 618 implants were inserted in the study group in order to prosthetic the edentulous gaps. Discussions. The study highlighted the high interest of females in the application of modern dental therapies. At the age group, the 50-59 age group was best represented, closely followed by the 40-49 age group. Most implants were inserted at the upper arch, at a right angle and were conical. Conclusions. Due to the lower bone density in the upper arch, 81.4% of failures occurred in the group studied in the jaw. Implants with small steps between turns have a better prognosis compared to implants with large steps between turns. From the point of view of the type of implant, the cylindrical-conical ones had the best prognosis, and the zygomatic ones registered the weakest prognosis. Bone additions were correlated with a higher failure rate (55.81% of cases). Implants inserted at 10˚ had the best survival rate, and those inserted at 35˚ and 55˚ had the lowest survival rate.